Depression as a risk factor for suicide: A systematic review (Research, Society and Development, 2021)
Objective: To analyze the relationship between depression as a risk factor for suicide. Methodology: The method of Systematic Literature Review was adopted, whose guiding question was "How does depression directly influence the increase in suicide rates"?  The research theme was searched in the Scientific Electronic Library Online (SCIELO) and in the U. S. National Library of Medicine (PUBMED) databases, through the implementation of the Health Sciences Descriptors (DeCS): ("suicide" AND "depression"). The inclusion criteria used were: presence of the DeCS, Portuguese or Spanish language, full text available, studies in humans, and cross-sectional studies. After applying the filters, only seven articles met the eligibility criteria. Results: It was evidenced by the authors that the rates of suicidal practices related to depression have increased significantly, being configured as one of the main causes of death and public health problems faced today. Conclusion: Through this study, it was revealed that the rates of suicidal practices related to depressive disorders are notoriously high, and that the existence of scientific and economic tools is necessary for the prevention of suicide cases in the global sphere.